The Influence of Product Reviews, Prices and Trust on Online Purchase Decisions at Shopee - Telli Poniman Chandra; Anny Nurbasari (International Journal Labs, 2022)
The digital industry in Indonesia is growing and increasing very rapidly, one of the growing industries is the e-commerce industry in Indonesia. Trust, researchers conducted research on Shopee. So this research is entitled